Thrombectomy and Stenting Management in Basilar Artery Occlusion Associated with Acute Stroke Case Report: Important Role of Radiology for Diagnostic and Treatment : Critical Role of Radiology in the Diagnosis and Management of Basilar Artery Occlusion Associated with Acute Stroke Case Report - Tjakraatmadja, Ricardo; Muda, Ahmad Sobri; Yueniwati, Yuyun; Abu Hassan, Hasyma; Nasir Aslam, Achmad Bayhaqi; Md Noh, Mohamad Syafeeq Faeez; Kamis, Mohd Fandi Al-Khafiz (Journal Of Cardiovascular, Neurovascular & Stroke, 2023)
Occlusions of the basilar artery (BA), which are typically caused by thromboembolism and atherosclerosis, may account for as much as 27% of posterior circulation ischemic strokes. The symptoms of BA occlusion can range from temporary weakness or paraesthesia to near-complete paralysis, leading to a high risk of morbidity and mortality. CT and MRI are the imaging modalities of choice for identifying and locating the infarct area, ruling out any other lesions, and detecting vascular abnormalities. The combination of thrombectomy and stenting has been shown to increase the safety and durability of angioplasty without causing noticeably negative side effects, and it may be utilized as the first line of treatment for BA stenosis or occlusion in acute stroke.